Immunomodulatory Effect of Red Guava Yogurt on Escherichia coli-Infected Mice - Kurniawati PD, Ania; Shavilla, Evy; Rachman, Hidayatul; Rachmat, Iqmal D; Pebrian, Noval Y (ACTA Medical Health Sciences, 2025)
Antibodies are a component of the adaptive immune system that plays a crucial role in preventing foreign pathogens that cause various infections. One effective way to enhance the immune response is through the consumption of probiotic-based fruit yogurt (fruitghurt). The purpose of this study is to determine the effect of administering red guava juice-based fruitghurt on the immune response of mice induced by Escherichia coli bacteria. This research used is a laboratory experimental design. The subjects consisted of Mus musculus mice, which were divided into 3 groups: positive control group, negative control group, and treatment group. Data were analyzed using one-way analysis of variance (ANOVA), and post hoc comparisons conducted via Tukey’s test to determine specific intergroup differences. The results demonstrate a statistically significant rise in antibody titers among mice receiving fruit yogurt treatment compared to control groups. The observed increase in antibody titers may be attributed to the immunomodulatory effects of Lactobacillus acidophilus, the micronutrient content of red guava, and immune stimulation induced by Escherichia coli exposure. Furthermore, Lactobacillus acidophilus enhances macrophage activity and antigenic presentation, thereby stimulating B lymphocytes to produce antibodies. Concurently, the micronutrients in red guava promotes the proliferation and differentiation of B lymphocytes, further enhancing antibody synthesis. Collectively, these findings demonstrate that yogurt fermented with Lactobacillus acidophilus and enriched with red guava juice exerts significant immunomodulatory effects. This functional food intervention enhances antibody titers, lymphocyte counts, and macrophage activity in Escherichia coli-infected mice, underscoring its potential as a dietary strategy to bolster immune responses against bacterial infections. DOI : 10.35990/amhs.v4n1.p41-50 REFERENCES Masud Parvez GM, Uzzaman S, Miah Akanda K, Mehjabin S. A short review on a nutritional fruit: guava. Open Access Toxicol Res. 2018;1(1):1–8. Yang Y, Greenleaf Z, Kann W, Sha M. Microaerobic fermentation of Lactobacillus acidophilus within gut microbiome physiological conditions by BioFlo® bioprocess control stations. Appl Eppend Note. 2019;(412):1–8. Yousefi B, Eslami M, Ghasemian A, Kokhaei P, Salek-Farrokhi A, Darabi N. Probiotics importance and their immunomodulatory properties. J Cell Physiol. 2019;234(6):8008–18. Rusli, Amalia F, Dwyana Z. Potential of Lactobacillus acidophilus bacteria as antidiare and immunomodulator. J Biol Makassar. 2018;3(2):25–30. Creswell JW. Research design. 4th ed. Thousand Oaks (CA): SAGE Publications; 2014. 342 p. Dewi AKP, Nawangsih EN. Pengaruh penambahan sukrosa dalam media jambu biji merah terhadap TPC Lactobacillus acidophilus pada penyimpanan suhu refrigerator. Fak Kedokt Univ Jenderal Achmad Yani. 2015;55–8. Tejada-Simon MV, Lee JH, Ustunol Z, Pestka JJ. Ingestion of yogurt containing Lactobacillus acidophilus and Bifidobacterium potentiates immunoglobulin A responses to cholera toxin in mice. J Dairy Sci. 1999;82(4):649–60. Widianingsih M, Kurniawati PDA, et al. Efektifitas probiotik single dan multi strain terhadap Escherichia coli secara in vitro. J Sains Teknol. 2018;71(6):885–94. Aattouri N, Bouras M, Tome D, Marcos A, Lemonnier D. Oral ingestion of lactic acid bacteria by rats increases lymphocyte proliferation and interferon-γ production. Br J Nutr. 2002;87(4):367–73. Gutiérrez RMP, Mitchell S, Solis RV. Psidium guajava: A review of its traditional uses, phytochemistry and pharmacology. J Ethnopharmacol. 2008 Apr 17;117(1):1–27. Subowo. Imunobiologi. 4th ed. Jakarta: Sagung Seto; 2021. Hall JE, Guyton AC. Guyton dan Hall buku ajar fisiologi kedokteran. Philadelphia: Saunders Elsevier; 2011. 1091 p. Marcos A. Editorial: A review of micronutrients and the immune system—working in harmony to reduce the risk of infection. Nutrients. 2021;13(11). Erkelens MN, Mebius RE. Retinoic acid and immune homeostasis: a balancing act. Trends Immunol. 2017 Mar 1;38(3):168–80. World Health Organization, Food and Agriculture Organization. Health and nutritional properties of probiotics in food including powder milk with live lactic acid bacteria [Internet]. 2001 [cited 2023 Feb 4]. Available from: https://www.fao.org/3/a0512e/a0512e.pdf Nanjundaiah YS, Wright DA, Baydoun AR, Khaled Z, Ali Z, Dean P, et al. Modulation of macrophage function by Lactobacillus-conditioned medium. Front Cell Dev Biol [Internet]. 2020 Jul 30 [cited 2023 Feb 4];8. Available from: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7406691/ Todar K. Lactobacillus acidophilus [Internet]. University of Wisconsin; 2020 [cited 2022 Jul 30]. Available from: https://textbookofbacteriology.net/index.html Artanti D, Sari YES, Azizah F, Puwaningsih NV, Rohmayani V, Nasrullah D. Effect of giving probiotic supplement Lactobacillus acidophilus La-14 as an immunomodulator to maintain a respiratory system in Mus musculus. Iran J Microbiol. 2021 Jun;13(3):381–8. Rocha-Ramírez LM, Pérez-Solano RA, Castañón-Alonso SL, Moreno Guerrero SS, Ramírez Pacheco A, García Garibay M, et al. Probiotic Lactobacillus strains stimulate the inflammatory response and activate human macrophages. J Immunol Res. 2017;2017:1–9. Dewi AKP, Pratiwi ST, Hasan K, Sasongko S, Hanif Y, Pardosi DV. Uji organoleptik dan karakteristik fisikokimia fruitghurt sari jambu biji merah (organoleptic test and physicochemical characteristics of fruitghurt red guava). Medika Kartika J Kedokt Kesehat. 2018;4:1–7. Agnesa OS, Susilo H, Lestari SR. Aktivitas imunostimulan ekstrak bawang putih tunggal pada mencit yang diinduksi Escherichia coli. Pharmaciana. 2017 May 8;7(1):105–12. Kopp-Hoolihan L. Prophylactic and therapeutic uses of probiotics: a review. J Am Diet Assoc. 2001 Feb;101(2):229–38. Van Gorkom GNY, Klein Wolterink RGJ, van Elssen CHMJ, Wieten L, Germeraad WTV, Bos GMJ. Influence of vitamin C on lymphocytes: an overview. Antioxidants. 2018;7(3):1–15. Sathawane P, Kamal MM, Deotale PR, Mankar H. Nuances of the Papanicolaou stain. Cytojournal. 2022;19:43. Alberts B, Johnson A, Lewis J, Raff M, Roberts K, Walter P. Lymphocytes and the cellular basis of adaptive immunity. In: Molecular biology of the cell. 4th ed. New York: Garland Science; 2002. p. 1201–55.